Pengaruh Ukuran Partikel dan Waktu Maserasi terhadap Ekstrak Virgin Coconut Oil (VCO) Kunyit (Curcuma longa L.) sebagai Pewarna Alami - Oktavian, Aldi; Suhendra, Lutfi; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
Turmeric contains a carotenoid that can be used as a natural dye by extracting a carotenoid compound using VCO. This research is meant to know the effect of particle size and time of maseration to VCO turmeric extract as natural dye and to determine the impact the best particle size and time of maseration to produce VCO turmeric extract as natural dye. This experiment used a random group design with two factors. First factor is particle size which is composed of   40, 6 0, and 80 mesh . Second factor in time of maseration which is composed of 4, 6 dan 8 hours. Data is analyzed with variance analysis and followed by Tukey test. Research shows interactions between particle size and time of maseration have very real impact on carotenoid total, betacarotene level, and the reddish level. Interagency interaction have real impact on brightness level but have no real impact on yield and yellowish level. Best treatment to produce VCO turmeric extract as natural dye are with 40 mesh for particle size and 6 hours for time of maseration with characteristic of yield 73,26 ± 0,15 percent, carotenoid total in the amount of 205,78± 0,40 µmol/L , betacarotene level in the amount of 9,99± 0,07 mg/g , brightness level 43,06± 1,02 , reddish level 15,31±0,95 , and yellowish level 42,33±0,61 . Keywords : T urmeric, VCO, extraction, carotenoid, natural dye